Assessing a national work health and safety policy intervention using the psychosocial safety climate framework - Potter, Rachael E.; Dollard, Maureen F.; Owen, Mikaela S.; O'Keeffe, Valerie; Bailey, Tessa; Leka, Stavroula (Elsevier, 2017)
Despite support for work health and safety (WHS) policy interventions, the evaluation of their effectiveness has been overlooked. As such, many important policy developments have not been assessed for their impact within jurisdictions and organisations. We addressed this research gap by using the Psychosocial Safety Climate (PSC) framework, theory, measurement tool – the PSC-12, and benchmarks - to investigate the impact of a WHS policy intervention, across Australian jurisdictions, that standardised policy approaches (i.e. harmonisation) and legislated the protection of psychological health. PSC refers to a facet of organisational climate that relates to psychological health and safety and is a predictor of job design and employee health. We investigated perceived organisational PSC across jurisdictions, across time, and contrasted effects between those that did (harmonised) and did not (non-harmonised) adopt the policy. Results showed Time X Group effects for the global PSC measure, indicating a significant difference over time between the harmonised and non-harmonised jurisdictions. Specifically, PSC levels significantly decreased in the non-harmonised jurisdiction over time. Analysis of PSC subscales showed that a significant decline in management commitment and priority, and communication (marginally) in relation to employee psychological health, within the non-harmonised group underpinned these effects. We noted no significant overall PSC change across the harmonised jurisdictions, with the exception that participation and consultation in relation to employee psychological health significantly increased. Results imply that without harmonisation the PSC levels reduced. Future research should seek detailed information regarding policy implementation, regulator perspectives and employer data to compliment results from the PSC-12.